Grief experiences of nurses who lose their first-degree relatives with the diagnosis of COVID-19: A qualitative study. - Ordu, Yadigar; Yılmaz, Sakine (Death Studies, 2024)
The grief experiences of healthcare professionals have both short- and long-term effects. This qualitative study was conducted between December 2022 and January 2023 to examine the grief experiences of nurses who lost their first-degree relatives to COVID-19. In this study, 22 nurses working in hospitals in Turkey were selected through a snowball sampling process. Data were collected with the "Nurse Information Form" and "Semi-Structured Interview Form." Nurses were interviewed individually approximately 30 minutes. Collaizzi's phenomenological analysis and MAXQDA 2020 software were used to analyze the data. A COREQ Statement Checklist was followed in the preparation of this study. The following five themes were identified: (1) Complex and deep feelings, (2) An inevitable end, (3) An innocent death, (4) Secluded funerals and rituals that could not be performed, and (5) Endless mourning. It is recommended to plan methods to protect nurses' psychosocial health and maintain their hopes during the grieving process.